Consensus expert recommendations for identification and management of asparaginase hypersensitivity and silent inactivation - van der Sluis, Inge M. (Haematologica, 2016)
L-asparaginase is an integral component of therapy for acute lymphoblastic leukemia. However, asparaginase-related complications, including the development of hypersensitivity reactions, can limit its use in individual patients. Of considerable concern in the setting of clinical allergy is the development of neutralizing antibodies and associated asparaginase inactivity. Also problematic in the use of asparaginase is the potential for the development of silent inactivation, with the formation of neutralizing antibodies and reduced asparaginase activity in the absence of a clinically evident allergic reaction. Here we present guidelines for the identification and management of clinical hypersensitivity and silent inactivation with Escherichia coli- and Erwinia chrysanthemi- derived asparaginase preparations. These guidelines were developed by a consensus panel of experts following a review of the available published data. We provide a consensus of expert opinions on the role of serum asparaginase level assessment, indications for switching asparaginase preparation, and monitoring after change in asparaginase preparation.